An Analysis of Aggression in Suzanne Collins’ The Hunger Games - Naning Choirunnisa (Politeknik Negeri Padang, 2020)
This article aims to analyse the aggression that is done by the tributes of the hunger games; they are Katniss, Peeta, Cato, Clove, Glimmer, and Thresh. The writer focuses on pointing out two topics, firstly the depiction of aggression in Suzanne Collins’ The Hunger Games, secondly the reason of aggression happened as depicted in Suzanne Collins’ The Hunger Games. The method used in this article is the concept of aggression by several experts to depict the aggression that is done by the tributes in the hunger games and the psychological approach of death instinct by Sigmund Freud and also the concept of aggression by Anderson & Bushman to find out the situational factors on the action of the aggression. The majority of the factors behind the action of aggression is following by the death instinct for destruction and the aggression is also because of the situational factors, such as aggressive cues, provocation, frustration, pain and discomfort, incentives, and drugs.Keywords: Aggression; death instinct; situational factors.